Maternal obesity is independently associated with increased antenatal admissions and health service costs. (18th April 2012) - Denison, FC; Lee, AJ; Morris, C; Mahmood, T; Norman, JE; Bhattacharya, S; Norwood, P; Scotland, G
Abstract : Aim: To determine the effect of maternal body mass index (BMI) on inpatient costs for all pregnancies in Scotland, and outpatient costs for a separate cohort. Methods: All women with singleton pregnancies, and estimable BMI, who delivered in Scottish maternity units between 01/01/2003 and 31/12/2009 were included (285, 361 admissions, 123, 931 pregnancies, 109, 291 women). Duration of stay and provider data were combined with hospital level unit cost data to estimate the cost of each admission and total admission cost for each pregnancy. Outpatient costs were analysed in a separate cohort of women delivering in Edinburgh (n=5052). Women were grouped using WHO BMI criteria. The reference group for all analyses was BMI 18.5<25kg/m2. Data were analysed by ANOVA and a Generalised Linear Model adjusted for age, deprivation, hospital, smoking status. Results: Mean (SD) number of admissions/pregnancy in underweight, normal, overweight, obese and morbid obesity were 2.40 (2.10), 2.14 (1.83), 2.3 (2.04), 2.64 (2.39), and 3.09 (2.87). Corresponding mean (SD) admission days were 3.58 (4.46), 3.31 (3.60), 3.47 (3.71), 3.79 (4.06) and 5.16 (3.97), respectively (p<0.01). Adjusted additional admission costs (mean (95% CI)) associated with underweight, overweight, obesity and morbid obesity were £172 (85-258), £157 (129-185), £474 (436-512) and £865 (767-963), respectively. Although attenuated, the U-shaped relationship between admission costs and BMI remained after ajusting for obstetric complications. Outpatient costs were also significantly higher (mean diff (95%CI)) in overweight (£22 (11-13)), obese (£53 (38-67)) and morbid obesity (£145 (96-193)), and ultrasound costs higher in underweight (£30 (13-46)) and morbid obesity (£99 (79-120))(unadjusted P <0.01). Conclusion: Obesity has significant cost implications for maternity services independent of obstetric complications.